Reproducing inequality? Social capital, digital literacy, and SES in access to higher education - Wang, Shiwei; Alam, Gazi Mahabubul; Bashir, Karima; Lei, Miao (Springer Nature, 2025)
Access to higher education and high-quality sources has become a new focus in the digital transformation framework now that higher education is expanding. With a focus on the roles of digital literacy and socioeconomic status (SES), this study examines the influence of social capital on China’s high school graduates’ access to higher education. Regression and group regression analyses are used in this study to examine the mechanism shaping learning opportunities based on survey data from 629 students in China’s western, central, and eastern provinces. The results indicate that while social capital positively correlates with access to higher education across all groups, its advantages are more pronounced among high SES students, especially regarding entrance to elite universities. Furthermore, social capital is partially mediated by digital literacy. These findings highlight the importance of employing intervention measures to help students from underprivileged backgrounds and the varied methods shaping students’ learning prospects in China.